A Location-Allocation Model for Seaport-Dry Port System Optimization. (24th November 2013) - Feng, Xuejun; Zhang, Yan; Li, Yuwei; Wang, Wei
Abstract : Seaports participate in hinterland economic development through partnerships with dry ports, and the combined seaport-dry port network serves as the backbone of regional logistics. This paper constructs a location-allocation model for the regional seaport-dry port network optimization problem and develops a greedy algorithm and a genetic algorithm to obtain its solution. This model is applicable to situations under which the geographic distribution of demand is known. A case study involving configuration of dry ports near the west bank of the Taiwan Strait is conducted, and the model is successfully applied.